Clinical observation on the efficacy of non-lactating mastitis treated with staged surgery - QU Wenchao, WAN Hua, WU Xueqing, FENG Jiamei, XIE Lu, GAO Qingqian, SHAO Shijun, SUN Jiaye (Waike lilun yu shijian)
Objective To explore the clinical efficacy of staged surgery for non-lactating mastitis. Methods A retrospective analysis was conducted on 317 patients with non-lactating mastitis admitted to our department from January 2015 to December 2020, all of whom underwent staged surgical treatment. The recovery time, recurrence rate, and breast appearance score were observed. Results The median follow-up time was 24(17，33) months, the recovery time was (25.5±17.9) days, and the recurrence rate was 4.4%. There were 96.2% of patients satisfied with the breast appearance. Conclusions Staged surgery for non-lactating mastitis can effectively shorten the course of the disease, protect the appearance of breast, and have good clinical efficacy.